China - International Experience in Policy and Regulatory Frameworks for Brownfield Site Management - Gong, Yuyang (World Bank, 2012)
Recurring environmental incidents have led to increased public awareness of the threats of environmental pollution to public health and rapid urbanization is driving up land prices in Chinese cities. As a result of these developments, industrial plant relocations are numerous, particularly of heavily polluting industrial plants, such as pesticide, coke, steel plants, and chemical industry plants. These relocations are leaving behind many contaminated sites in the cities, sometimes with various pollutants, as well as complex and serious soil and groundwater contamination. It has become increasingly clear that China needs a comprehensive policy, regulatory, technical, financial, and management framework to effectively track, evaluate and clean up the numerous contaminated sites. Currently, China has no specific law regulating contaminated site remediation and management. Soil protection provisions do exist in some generic legislation, in the form of air and water protection laws, solid waste laws, and toxic substance control acts. However, due to their different objectives and scopes, they are often aimed at different aspects of the issue. As a result, existing provisions, even if fully implemented, may not fully cover the whole range of threats related to site contamination. Hence, learning from the experiences of other countries is essential for the Chinese government to increase its capacity and preparedness to manage issues related to site contamination.